Hypothetical Protein BPSL3393 of Burkholderia pseudomallei is Involved in Ethanolamine Catabolism - Ooi Gim Luan; Hokchai Yam; Razip Samian; Mustafa Fadzil Farid Wajidi; Nor Muhammad MahadI; Suriani Mohamad; Nazalan Najimudin (Tropical Life Sciences Research, 2017)
Burkholderia pseudomallei is a soil-dwelling bacterium that causes a globally emerging disease called melioidosis. Approximately one third of the in silico annotated genes in its genome are classified as hypothetical genes. This group of genes is difficult to be functionally characterized partly due to the absence of noticeable phenotypes under conventional laboratory settings. A bioinformatic survey of hypothetical genes revealed a gene designated as BPSL3393 that putatively encodes a small protein of 11 kDA with a CoA binding domain. BPSL3393 is conserved in all the B. pseudomallei genomes as well as various in other species within the genus Burkholderia. Taking into consideration that CoA plays a ubiquitous metabolic role in all life forms, characterization of BPSL3393 may uncover a previously over-looked metabolic feature of B. pseudomallei. The gene was deleted from the genome using a double homologous recombination approach yielding a null mutant. The BPSL3393 mutant showed no difference in growth rate with the wild type under rich and minimal growth conditions. An extensive metabolic phenotyping test was performed involving 95 metabolic substrates. The deletion mutant of BPSL3393 was severely impaired in its ethanolamine metabolism. The growth rate of the mutant was attenuated when ethanolamine was used as the sole carbon source. A transcriptional analysis of the ethanolamine metabolism genes showed that they were down-regulated in the BPSL3393 mutant. This seemed to suggest that BPSL3393 functions as a positive regulator for ethanolamine metabolism. Burkholderia pseudomallei adalah bakterium kediaman tanah yang menyebabkan penyakit muncul secara global yang dikenali sebagai melioidosis. Dianggarkan satu pertiga daripada gen siliko di dalam genom dikelaskan sebagai gen hipotesis. Kumpulan gen ini sukar untuk dicirikan secara fungsional, sebahagiannya disebabkan oleh ketiadaan fenotip yang ketara di bawah tetapan makmal konvensional. Kajian bionformatik gen hipotetikal menunjukkan gen yang ditetapkan sebagai BPSL3393 yang menguraikan protein kecil 11 kDA dengan domain mengikat CoA. BPSL3393 dipelihara dalam semua genom B. pseudomallei serta pelbagai spesies lain dalam genus Burkholderia. Dengan mengambil kira bahawa CoA memainkan peranan metabolik di mana-mana dalam semua bentuk kehidupan, pencirian BPSL3393 mungkin mendedahkan ciri metabolik B. Pseudomallei yang sebelum ini terlepas pandang. Gen ini dipadamkan dari genom menggunakan pendekatan penggabungan semula homolog berganda yang menghasilkan mutan null. Mutan BPSL3393 tidak menunjukkan perbezaan kadar pertumbuhan dengan jenis yang liar di bawah keadaan pertumbuhan yang kaya dan minima. Ujian fenotip metabolik yang meluas dilakukan dengan melibatkan 95 substrat metabolik. Pemotongan mutan BPSL3393 teruk terjejas dalam metabolisme etanolaminanya. Kadar pertumbuhan mutan itu dilemahkan apabila etanolamina digunakan sebagai sumber karbon tunggal. Analisis transkrip gen metabolisme etanolamina menunjukkan bahawa mereka telah dikawal dalam mutan BPSL3393. Ini seolah-olah menunjukkan bahawa fungsi BPSL3393 sebagai pengawal selia positif untuk metabolisme etanolamina.